Persepsi Remaja Mengenai Kesehatan Reproduksi, Kehamilan dan Pernikahan di Usia Remaja: Studi Kualitatif Pada Siswi SMA Pedesaan dan Perkotaan - Listyani Hidayati; Nunung Cipta Dainy; Eneng Nunuz Rohmatullayaly; Dodik Briawan (Universitas Muhammadiyah Surakarta, 2013)
Teenage pregnancy may result poor birth outcomes , such as the risk of stunting , infantmortality, premature and Low Birth Weight ( LBW ) . This study aimed to determine the perceptions ofhigh school girls in two different environments , namely rural and urban areas regarding teen pregnancy.The data included perceptions about nutrition and reproductive health , marriage and teen age pregnancy, premaritalpregnancy , as well as nutrition and health during pregnancy.This study was conductedin SMA Negeri 1 Lewiliang, Bogor Regency and SMA Negeri 1 Bogor City with total subjectsweresix people. The result of this study showed a similar perception of the reproductive health of youngwomenin both rural and urban area . Subjects from the countryside can still tolerate teenage marriageandpregnancy if there is readiness of teenagers. In contrast, the subjects in urban areas do not thinkofan excuse to get married in young age . Youngwomen in the village can express more detailaboutfoodthat should be consumed or avoided , including food relating to taboo. In addition, young womeninthe village can provide more in-depth opinion about health care during pregnancy.